Inflation differentials in EU new member states: An empirical evidence - Roman Horváth; Kamila Koprnická (Charles University in Prague, Institute of Economic Studies (IES), 2008)
In this paper, we examine the determinants of inflation differentials in a panel of the new European Union member states vis-à-vis the euro area in 1997-2007. Our main results are as follows. Exchange rate appreciation and higher price level in the new EU members is associated with narrower inflation differential vis-à-vis the euro area, while fiscal deficit and positive output gap seem to contribute to higher inflation differential. Nevertheless, the effect of price convergence on inflation differentials is found to be dominating in these countries suggesting that a country with price level 20% below the euro area average is likely to exhibit inflation nearly one percentage point above the euro area. Overall, our results indicate that real convergence factors rather than cyclical variation are more important for inflation developments in the new EU members, as compared to the euro area.
Keywords: E31; F41; 330; inflation differentials; price convergence; exchange rate; New EU members; panel data; Inflation; Vergleich; EU-Staaten (Osteuropa)